Threats and Risks Generated by Illegal Migration Flows and Their Control - Tarnu Lucian Ioan (Scientific Bulletin, 2015)
Migration has existed since the beginning of mankind. The phenomenon has not been ceased in time, but it has changed and acquired new forms. Migration processes are conducted simultaneously and they are increasing in many countries. One of the long term results of this development could be the emergence of multicultural societies, tending towards new concepts of citizenship or national state. Most of the developed countries have become diversified and multiethnic societies, and those who have not reached this level yet, have turned decisively in this direction.